Building Job Satisfaction: The Role of Compensation, Work Motivation, and Work Environment - Nadya Ayu Lestari; Dede Sri Rahayu; Nadia Ulfa Agustin Hilman; Galih Nugraha; Ati Rosliyati (Entrepreneurship Faculty, Universitas Garut, 2025)
This study aims to examine the influence of compensation, work motivation, and work environment on job satisfaction, both partially and simultaneously. The population in this study consists of RA teachers in the Kawalu District, Tasikmalaya City, with a sample of 62 respondents. The method used is a verificative analysis approach, and the data were analyzed using multiple linear regression. The findings of this research reveal four key results. First, compensation, work motivation, and work environment collectively positively influence job satisfaction. Second, individual compensation has a positive influence on job satisfaction. Third, work motivation has a positive influence on job satisfaction. Fourth, the work environment also has a positive influence on job satisfaction.